Evolution of Excise (Coffee, Tobacco and Beer) over the Years. Its Impact on Consumption for the Period 2010 – 2015 - Harremi, Marsida; Dr. Kostandin Nasto (European Journal of Multidisciplinary Studies, 2016)
This paper aims to make a brief description of the evolution of the excise group - products of coffee, cigarette and beer. An important part of the study also occupies a simple analysis that shows how consumption affects the excise in these groups - consumer products and their effects on the health of consumers. This analysis is based on data from Customs of the Republic of Albania on the imported quantity of coffee, tobacco and beer, for a period 2010 - 2015. The analysis we reach the conclusion that the reduction of the level of excise increase the amount of coffee imported as a result of higher consumption of this product. The cigarette product fluctuations in the level of excise, but in general terms we can say that the cigarette excise tax increase and consequently comes to the imported quantity is reduced. We can say that the reduction of imports have also affected other factors such as the implementation of the Anti - smoking and awareness raising of consumers for having harmful effects of consumption of this product. The same situation applies to the beer product. Reduction of excise affects directly to reduce the quantity of import of this product. Evolution of the levels of excise duty over the years, the group mainly products coffee, tobacco and alcoholic beverages (beer).
Keywords: Evolution of the levels of excise duty over the years, the group mainly products coffee, tobacco and alcoholic beverages (beer).